Lymphatic endothelial sphingosine 1-phosphate receptor 1 enhances macrophage clearance via lymphatic system following myocardial infarction - Li, Qinyu; Zhou, Caixia; Zhao, Kang; Duan, Yunhao; Yue, Jinnan; Liu, Xiuxiang; Wu, Jinjin; Deng, Shengqiong (Frontiers in Cardiovascular Medicine, 2022)
Lymphatic endothelial cell homeostasis plays important roles in normal physiological cardiac functions, and its dysfunction significantly influences pathological cardiac remodeling after myocardial infarction (MI). Our results revealed that sphingosine 1-phosphate receptor 1 (S1pr1) expression in cardiac lymphatic endothelial cells (LECs) was sharply changed after MI. It has been shown that S1pr1 tightly controlled LEC functions and homeostasis. We thus hypothesized that lymphatic endothelial S1pr1 might be involved in post-MI cardiac remodeling. We generated LEC-conditional S1pr1 transgenic mice, in which S1pr1 expression was reduced in cardiac LECs. We performed the left anterior descending coronary artery (LAD) ligation operation to induce MI in these mice. Cardiac functions and remodeling were examined by echocardiography analysis and serial histological analysis. Meanwhile, we performed adoptive cell transfer experiments to monitor macrophage trafficking in post-MI myocardium and their draining lymphatic system. Furthermore, in vitro cell culture experiments and mechanism studies were undertaken to uncover the molecular mechanism by which LEC-S1pr1 regulated cardiac inflammation and remodeling after MI. Our results showed that S1pr1 expression significantly decreased in cardiac LECs after MI. Our in vivo experiments showed that the reduced expression of LEC-S1pr1 deteriorated cardiac function and worsened pathological cardiac remodeling after MI. Our further results demonstrated that the reduced expression of LEC-S1pr1 did not influence macrophage infiltration in an early inflammatory phase of MI, but significantly affected macrophages clearance in the later phase of MI via afferent cardiac lymphatics, and thus influenced inflammatory responses and cardiac outcome after MI. Further study showed that S1P/S1pr1 activated ERK signaling pathway and enhanced CCL2 expression, which promoted macrophage trafficking in a paracrine manner. This study reveals that cardiac lymphatic endothelial cells tightly control macrophage trafficking via lymphatic vessels in injured hearts via S1P/S1pr1/ERK/CCL2 pathway and thus regulate post-MI immune modulation and heart repair. This study highlights the importance of cardiac lymphatic vessel system in orchestrating post-MI immune responses and cardiac remodeling by regulating macrophage transit in injured hearts. Our finding implies that a feasible modulation of S1pr1 signaling in LECs might provide a promising target to resolve excessive inflammation and to ameliorate adverse cardiac remodeling after MI.